In vitro antimicrobial activity of some plant extracts against Arcobacter butzleri and Arcobacter cryaerophilus - Adesiji, Yemisi Olukemi; Akanni, Racheal Adekemi; Adefioye, Olusegun Adelowo; Taiwo, Sunday Samuel (Acta medica Lituanica, 2012)
Background: There are increasing reports of resistance to current antibiotics employed in treatment of Arcobacter related infections. Materials and Methods: Carica papaya, Vernonia amygdalina, Ocimum gratissimum and Momordica charantia were tested against A. butzleri reference strain (ABSH3-1137) and A. cryaerophilus isolated from pig and chicken using disk diffusion technique. Results: The aqueous extract of C. papaya inhibited the growth of A. butzleri at inhibitory dose (ID) of 0.5 mg and the two A. cryaerophilus at ID of 1 mg while the methanol extract did not inhibit the growth of any strains. The aqueous and methanol extracts of V. amygdalina inhibited the growth of A. cryaerophilus isolated from pig and chicken at ID of 10 mg but did not inhibit A. butzleri. The methanol extracts of O. gratissimum inhibited A. butzleri and A. cryaerophilus pig isolate at ID of 2.5 mg and the chicken isolate at ID of 1 mg. The aqueous extracts of O. gratissimum inhibited A. butzleri, A. cryaerophilus of chicken isolate at ID of 5 mg, and A. cryaerophilus of pig isolate at 2.5 mg. The methanol extracts of M. charantia had ID of 2.5 mg for A. butzleri and A. cryaerophilus pig isolate and ID of 1 mg for A. cryaerophilus chicken isolate while the aqueous extracts had ID of 5 mg for all the three strains tested. Conclusions: The result obtained from this study showed that both aqueous and methanol extracts of four commonly used herbs in Nigeria inhibited the growth of Arcobacter species to a varying degree with the aqueous extract of C. papaya leaves reported in vitro highest antimicrobial activity and thereby may serve as potential sources for new antimicrobial agents against Arcobacter.